EVALUATION OF THE FUNCTIONALITY OF 3R WASTE MANAGEMENT FACILITIES IN GORONTALO PROVINCE - Rahmawati A. Damiti; Fitryane Lihawa; Dewi Wahyuni Baderan (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
The waste generation in Indonesia, including Gorontalo Province, reaches 199.53 tons per day, necessitating strengthened 3R Waste Processing Facilities (3R TPS) to achieve national targets of 30% waste reduction and 70% waste management. This study analyzes the functionality of 3R TPS using a qualitative case study approach in Gorontalo City, Bone Bolango Regency, and Pohuwato Regency. Data were collected through in-depth interviews, participatory observation, and document analysis. Results indicate that only 12 of 30 3R TPS (40%) are operational. Planning factors constitute the main constraints, including noncompliance with sanitation zoning, service coverage below the minimum threshold of 800 inhabitants, and limited accessibility of approximately ±15 km from district centers. From the management perspective, facilities show high dependency on government support, inconsistent user fee systems, and low community participation. Institutional functions remain suboptimal, particularly in Bone Bolango, where several facilities lack formal organizational structures. In contrast, Pohuwato Regency represents a best practice through salary incentives of IDR 1,250,000 per month and collaborative partnerships managing approximately 20 tons of waste annually. SWOT analysis positions the 3R TPS in Quadrant I, indicating strong opportunities that support aggressive strategies focused on institutional strengthening, infrastructure optimization, and expanded partnerships to enhance the effectiveness and resilience.